Pengembangan E-Modul pada Pembelajaran Geografi untuk Meningkatkan Literasi Lingkungan Siswa - Eli Wahyuni; Amalia Novarita; Rahmawati Rahmawati; Suwarni Suwarni (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
This research was motivated by the limited availability of effective and engaging teaching materials, as well as the lack of e-modules in the learning process, particularly in Geography subjects. The urgency of this study lies in the importance of environmental literacy as a key competency for students to address global challenges. Therefore, the objective of this research was to develop a Geography e-module aimed at enhancing students’ environmental literacy. The research employed a Research and Development (R&D) design using the ADDIE model, although it was limited to three stages: analysis, design, and development. Validation results showed that the developed e-module received an assessment score of 78.12% from media experts, 92.03% from material experts, and 80% from practitioners/Geography teachers. Meanwhile, the small group trial obtained a score of 85.91%. Based on the one-sample t-test conducted to measure students’ environmental literacy, the significance value was 0.001 (p < 0.05). This indicates that Ha was accepted, meaning that the average post-test score of students (86) was significantly higher than the reference value (61). This result falls into the “very good” and “effective” category. In conclusion, the developed Geography e-module was proven to be feasible, valid, and effective in improving students’ environmental literacy. This product can serve as an innovative solution in learning and contributes to the advancement of sustainable education.